Faktor -Faktor Yang Berhubungan dengan kejadian Ruptur Perineum pada persalinan Pervaginam Diklinik Budi Mulia Palembang Tahun 2024 - Tirta Anggraini; Leny; Arly (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2024)
ABSTRACT Perineal rupture is a perineal tear that occurs when a baby is born either spontaneously or with the use of tools or actions., there are four levels of perineal tears. Extensive perineal tears can cause heavy bleeding, and if not treated properly can increase maternal morbidity and mortality. The Maternal Mortality Rate according to the limits of The Tenth Revision of The International Classification of Diseases (ICD - 10) is the death of women that occurs during pregnancy until the end of the postpartum period or within 42 days after the end of pregnancy. (Arulita, 2018). According to the World Health Organization (WHO), UNICEF and UNFPA, (2014) every day there are 830 cases of maternal death. There are 2.7 million cases of perineal rupture in women giving birth, estimated to reach 6.3 million in 2050. While in Asia the incidence of perineal rupture in society, 50% of the incidence of perineal rupture in the world Purpose of the study: to determine what factors are associated with the incidence of perineal rupture in women giving birth vaginally at the Budi Mulia Sriwijaya Clinic in 2024. Methodology: this study is an analytical study with a cross-sectional approach. The data used are secondary data taken from the medical records of mothers who gave birth at the Budi Mulia Medika Clinic from September to December 2024 as many as 30 respondents. The sampling technique used is total sampling. The statistical test used is Chi Square with the results of the study: showing that there is no relationship between maternal age and the incidence of perineal tears with a value of p = 0.825, there is a relationship between maternal parity and the incidence of perineal tears with a value of p = 0.010, there is a relationship between infant weight and the incidence of perineal tears with a value of p = 0.016. Conclusion: birth weight and parity are risk factors for perineal rupture. Keywords: Age, Parity, Birth Weight, Perineal Ruptur